2017
DOI: 10.3386/w23945
|View full text |Cite
|
Sign up to set email alerts
|

The Ostrich in Us: Selective Attention to Financial Accounts, Income, Spending, and Liquidity

Abstract: This paper investigates attention to personal financial accounts using panel data from a financial management software provider containing information on daily logins, income, spending, balances, and credit limits. We first explore whether individuals pay attention in response to the arrival of income payments. Here, we utilize that weekends and holidays generate exogenous variation in regular payment arrival using a fixed-effects approach. We find that individuals are five times more likely to log in on days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Importantly, these increases are not driven by trading activity of the cryptocurrencies themselves; rather, investors increase trading activity in other, non-cryptocurrency related assets as well. This is consistent with recent literature on anticipation and trading activity (Olafsson and Pagel, 2019;Sicherman, et al, 2015), and echoes findings on the trend-chasing and overtrading behavior of retail investors (Barber and Odean, 2007).…”
supporting
confidence: 92%
“…Importantly, these increases are not driven by trading activity of the cryptocurrencies themselves; rather, investors increase trading activity in other, non-cryptocurrency related assets as well. This is consistent with recent literature on anticipation and trading activity (Olafsson and Pagel, 2019;Sicherman, et al, 2015), and echoes findings on the trend-chasing and overtrading behavior of retail investors (Barber and Odean, 2007).…”
supporting
confidence: 92%
“…the fact that I might pay more attention to things that favor or are pleasing to me (a self-serving bias), and avoid depressing thoughts. There is empirical evidence for this; for instance Olafsson and Pagel (2017) find that people are more likely to look at their banking account when it is flush than when it is low, an "ostrich effect" (Karlsson et al 2009;Sicherman et al 2016). The evidence is complex: in loss aversion, people pay more attention to losses than gains, something prima facie opposite to a selfserving attention bias.…”
Section: Motivated Attentionmentioning
confidence: 99%
“…Yet another model is that people might be monitoring information but are mindful of their loss aversion, i.e. avoid "bad news", along the lines of Kőszegi and Rabin (2009), Olafsson and Pagel (2017) and Andries and Haddad (2017).…”
Section: Motivated Attentionmentioning
confidence: 99%
“…I then outline the implications of signals with information content high enough to affect the investor's attentiveness and consumption behavior. I find that adverse signals induce the investor to ignore his portfolio; he is selectively attentive and subject to the "Ostrich effect" (Karlsson, Loewenstein, and Seppi (2009) and Olafsson and Pagel (2017) among others).…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, transaction and information costs do not explain expensive delegated portfolio management, time diversification, or mental accounting. Furthermore, Sicherman, Loewenstein, Seppi, and Utkus (2015) and Olafsson and Pagel (2017) showed that inattention to financial accounts appears to be highly selective, that is, driven by information-or belief-based utility theories, rather than rational, that is, driven by mechanical costs and benefits. 3 In contrast, Andries and Haddad (2017) generated inattention with disappointment-averse preferences in a continuous-time portfolio-consumption model.…”
Section: Introductionmentioning
confidence: 99%